Oxidation of Enrofloxacin with Permanganate: Kinetics, Multivariate Effects, Identification of Oxidation Products, and Determination of Residual Antibacterial Activity - Yongpeng Xu; Shiyao Liu; Fang Guo; Fuyi Cui (Journal of Chemistry)
Permanganate [Mn(VII)] chemistry oxidation of fluoroquinolone (FQ) antibiotic enrofloxacin (ENR) in water is investigated with respect to the kinetics, pH effect, buffer effect, and the evaluation of residual antibacterial activity after oxidative treatment. The degradation of ENR by Mn(VII) obeyed a secondary-order kinetics. Modern high-resolution tandem mass spectrometry coupled with high performance liquid chromatography was used to analyze the structures of degradation products. Four main oxidation products were identified at different pH values. Several influencing factors, pH value, and buffer obviously affect reaction rate and products relative abundance. Autocatalysis taking place at slightly acidic pH promotes the reaction but has no effect on the product types. A plausible oxidation pathway for enrofloxacin with Mn(VII) was proposed. The oxidation took place at the piperazine ring. Structural changes to the piperazine ring include N-dealkylation, hydroxylation, and hydrolysis. Residual antibacterial activity of the oxidative reaction solutions against nonresistant Escherichia coli reference strain DH5α is evaluated by means of quantitative bioassays. It is noticed that the oxidation products exhibited negligible antibacterial activity just when the structures of the products changed.